Perencanaan Strategik Sarana Prasarana di SMA Al Falah Ketintang Surabaya - Rosyidi, Muhammad; Veroniva, Junia Thre; Jariyah, Ainun; Aj-Jaudah, Salsabila; Ghorizah, Fithrotul; Wulandari, Ayu; Nuphanudin, Nuphanudin (Universitas Ahmad Dahlan, 2023)
Penelitian ini yang berjudul